Perilaku Birokrasi Terhadap Kualitas Pelayanan Kependudukan - Kisman Karinda; Wildan Zaman (Journal of Government Insight, 2021)
This paper aims to determine the Bureaucratic Behavior on the Quality of Population Services in the Luwuk District, Banggai Regency. The method of writing uses descriptive explanatory with quantitative analysis of instrument trials and two data collections in the context of actual research. To obtain data on Bureaucratic Behavior on Population Service Quality to be collected, processed and analyzed, using several data collection methods through observation, interviews, questionnaires and documentation, instruments used in documentation techniques. Based on the questionnaires' distribution to respondents, Bureaucratic Behavior on the Quality of Population Services in the Luwuk District, Banggai Regency, based on the rating scale, is classified as good with an average score of 75.24%.